The Yahweh-Baal Confrontation and Other Studies in Biblical Literature and Archaeology: essays in honour of Emmett Willard Hamrick; when religions collide - O'Brien, Julia M.; Hamrick, Emmett Willard (Studies in the Bible and early Christianity, 1995)
Essays include: When Religions Collide: The Yahweh/Baal Confrontation (Lawrence E. Toombs); Isaiah 40-55: A New Creation, A New Exodus, A New Messiah (John I. Durham); Historical Inquiry as Liberator and Master: Malachi As A Post-Exilic Document (Julia M. O'Brien); Problems of The Semitic Background of The New Testament (Joseph A. Fitzmyer, S.J.); Tell El-Hesi: What's in A Name? (Jeffrey A. Blakely and Fred L. Horton, Jr.); Bathing in the Face of the Enemy: A Late Byzantine Bath Complex in Field E Of The Joint Expedition To Caesarea Maritima (Fred L. Horton, Jr.). Also contains two appreciations of Emmett Willard Hamrick and a selected bibliography of Hamrick's writings.